Hubungan Antara Optimisme dan Dukungan Sosial Guru dengan Resiliensi Akademik pada Siswa SMKN 1 Batealit - Hakim, Muhammad Arif Rahman; Mahardayani, Iranita Hervi (Universitas Cokroaminoto Palopo, 2024)
This study is motivated by the phenomenon that many students of SMK N 1 Batealit unconsciously have low academic resilience, with several influencing factors including optimism and teacher social support. The purpose of this study was to empirically determine the relationship between optimism and teacher social support on academic resilience in students of SMK N 1 Batealit. The population of this study was a group of 12th grade students of SMK N 1 Batealit totaling 12 classes which included automotive engineering, accounting and financial institutions, culinary, office management and business services, agribusiness of agricultural product management, and agribusiness of agricultural and horticultural technology, with cluster random sampling technique involving 60 students. This research uses a quantitative approach with a correlation method. Data collection tools are academic resilience scale, optimism scale, and teacher social support scale. The results of data analysis showed the coefficient value of R=0.532, F=6.705, and p=0.004 (p<0.05). The findings concluded that optimism and teacher social support together have a significant relationship to academic resilience in students of SMK N 1 Batealit.